Biophysical implications of the freshwater influx over small spatial scale in the coastal waters along the southwest coast of India during the Southwest Monsoon. (1st February 2021) - Santhikrishnan, S.; Jyothibabu, R.; Albin, K.J.; Alok, K.T.; Karnan, C.; Arunpandi, N.; Camey, M.F.; Gireesh Kumar, T.R.
Abstract: This study in the coastal waters off Kochi along the southwest coast of India during the Southwest Monsoon (SWM) presents the biophysical implications of freshwater influx over a small spatial scale. Field sampling was carried out along two cross-shore transects (ST and NT), oriented ~ 8 km apart, and located to the south (ST) and north (NT) of the Kochi inlet, up to the depth of 50 m. The vertical profiles of temperature and dissolved oxygen showed clear upwelling signatures along both ST and NT, but more prominently along the latter transect. The freshwater influx and its southward advection due to the prevailing coastal currents caused stronger salinity stratification along ST and inhibited the rising of upwelled waters in the nearshore waters. The integrated phytoplankton biomass (chlorophyll a ) in the upper 10 m was markedly higher along NT (50 mg m −3 ) compared to ST (35 mg m −3 ). The size-based phytoplankton biomass showed an increase in larger size (micro) fraction of phytoplankton along NT especially in the nearshore waters, wherein upwelling was prominent up to the surface waters. The more efficient surfacing of oxygen-deficient waters along NT cause more likely chances to concentrate small pelagic fishes there as compared to ST. Thus, this study presents a case, wherein, the freshwater influx and associated inhibition of coastal upwelling in the nearshore waters vary within a short spatial scale depending upon the advection of freshwater plume by the coastal currents. Also, showed that this situation might be valid to many estuarine inlet regions along the southwest coast of India during the SWM. Highlights: This study was carried out in the coastal waters off Kochi, India. Presented the biophysical implications of freshwater influx and upwelling. Freshwater influx inhibited the coastal upwelling. Relatively small phytoplankton was favoured by freshwater plume. But, upwelling favoured relatively large phytoplankton.